Human and animal health in nomadic pastoralist communities of Chad: Zoonosis, morbidity and health services - Schelling, E. (University of Basel, 2002)
The health of nomadic pastoralists is influenced by factors specific to their way of life. Nomadic pastoralists depend on their livestock for subsistence, especially on the livestock’s milk. Veterinary services provide vaccination against feared livestock diseases such as anthrax. Agents transmissible between livestock and humans (zoonotic agents) may have an important impact on the health status of pastoralists because they live in close contact to their animals. However, morbidity of nomadic pastoralists in Chad had not been documented and their everyday use of health services was virtually unknown. A research collaboration between veterinary and public health was implemented to evaluate morbidity of nomadic pastoralists and of their animals simultaneously and to test intersectoral pilot-interventions following the concept of “one medicine”. The studies encompassed in this thesis were conducted in the framework of an interdisciplinary research and action programme. Fulani and Arab cattle breeders and Arab camel breeders were visited during three consecutive samplings, two in the dry season and one in the wet season, between April 1999 and April 2000. A physician clinically examined 1160 women, men and children and completed a survey questionnaire. Sera, sputum and urine samples were collected from humans, as well as sera and milk from 1640 animals. Complementary interviews mainly directed at livestock health were recorded. Brucellosis and Q-fever were selected to investigate a possible correlation between the occurrence of these zoonoses in livestock and in humans. No active foci of brucellosis were found. The impact of brucellosis and Q-fever on the health status of the three nomadic communities included in the study appeared marginal in comparison to other diseases recorded. Pulmonary diseases were frequent, e.g. bronchitis in children under 5 years of age (18%). Arab cattle and camel breeders were severely diseased by malaria during the wet season. Clinically diagnosed malaria was prevalent during the entire year among Fulani, who stayed in the vicinity of Lake Chad. Human serum retinol concentrations were significantly correlated to livestock milk retinol, illustrating the significance of milk as a dietary component. However, serum retinol levels of women were generally low. A 24-hours dietary recall showed that nomadic pastoralists only rarely consumed fruits and vegetables. The utilisation study provided an overview on health service utilisation patterns of sick nomadic pastoralists. Participants with respiratory disorders went early to a dispensary for consultation and successively also used more other health services. Dispensaries where antimalarial drugs were known to be in short supply were rarely visited during the wet season. Our data suggest that young unmarried women and men had fewer opportunities to visit a marabout or a dispensary than other members of the community. Women gave birth assisted by relatives in the camps, and prenatal health care was virtually not used. No fully immunised nomadic child was found in the study population. In contrast, livestock had been vaccinated by veterinarians visiting the nomadic camps during compulsory vaccination campaigns. Breeders observed an increasing inefficacy of anthrax, blackleg and pasteurellosis vaccines. Deaths of cattle after vaccination against contagious bovine pleuropneumonia and visits of veterinarians solely to take blood for rinderpest serosurveillance without treating diseased animals were recurrent complaints of nomadic pastoralists towards veterinary services. Nevertheless, the idea of joint human and animal vaccination campaigns was appreciated because nomadic pastoralists wanted vaccination for their children, especially against measles. To which extent knowledge and experiences with livestock vaccination were transposed to children vaccination remained unclear. A cost analysis of subsequent joint vaccination campaigns showed that the public health sector can save up to 15% of infrastructure and personnel costs when vaccination services for nomadic children and women are delivered together with interventions of the livestock production sector. Improvement of the quality of dispensary services has a potential to increase the utilisation of dispensaries by nomadic people. Health workers belonging to the nomadic community itself and better able to reach the camps may, nevertheless, be more accessible to women and children. Static or outreach dispensary-based vaccination services do not have the same efficiency to reach nomadic children as mobile vaccination campaigns have. Private veterinarians, who almost exclusively have access to pastoralists in remote areas would be interested in more fully capitalising their transportation infrastructure. Joint human and animal vaccination campaigns should be extended to other services (such as the selling of drugs) and especially to information campaigns. The provision of appropriate information may be as important as health care interventions themselves.